Legal Protection for Notaries in Semarang City Area - Luthfi Sidiq, Muhammad; Sri Darmadi, Nanang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Paragraph IV of the Preamble to the 1945 Constitution, among others, states that the Government of the Republic of Indonesia protects all Indonesian people, advances public welfare, and educates the nation's life. The need for the community in the Semarang city area for legal certainty is a very important thing in life so that every element in society that is directly or indirectly related to implementing and enforcing the law must have the same parameters, namely achieving legal certainty. The Notary Law has regulated the form of legal protection that can be given to those who carry out their duties as public officials, this is reflected or stated in Article 66 paragraph (1), (2) of the UUJN and maintaining the right to refuse and the obligation to refuse the right must also be respected. Only the Courts and the Police have the right to summon the Notary concerned. This type of research uses empirical laws.This research approach uses a qualitative approach. The source of the type of data used in this study is primary data obtained through observation and interviews. The analysis in this study is descriptive analysis. The results of this study conclude that: 1).Legal protection for notaries in carrying out their duties as public officials based on the Notary Law in the Semarang City area in making authentic deeds must pay attention to the principles of caution, accuracy, and uphold honesty, morality and not forget professionalism. 2). The form of legal protection for Notaries who carry out their duties as legal officials in the City of Semarang must go through the Regional Supervisory Council because the Regional Supervisory Council (MPD) has a very important role in providing legal protection to notaries at the regional level, as well as ensuring that the procedure for taking minutes of deeds and other documents is carried out legally and in accordance with applicable legal provisions.